2017
DOI: 10.1039/c7tc02254a
|View full text |Cite
|
Sign up to set email alerts
|

Contorted tetrabenzoacenes of varied conjugation: charge transport study with single-crystal field-effect transistors

Abstract: A series of nonplanar tetrabenzo-fused acenes exhibited a hole mobility from 0.044 cm2 V−1 s−1 up to 0.81 cm2 V−1 s−1 in their single crystal field-effect transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Chemical Structures of Synthesized HBCs Scheme 1. Preparation of 3, 10,15,d,g,j,m,p] respect to the other two benzenes (fused at g-and p-positions), presumably due to the electronic and steric effects exerted by different functional groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Chemical Structures of Synthesized HBCs Scheme 1. Preparation of 3, 10,15,d,g,j,m,p] respect to the other two benzenes (fused at g-and p-positions), presumably due to the electronic and steric effects exerted by different functional groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…() In a recent experimental investigation, Huang et al reported the synthesis and charge transport properties of a series of contorted and polyfused aromatic tetrabenzoacenes and measured mobility up to 0.81 cm 2 V −1 s −1 . () Similarly, McGarry et al showed the ambipolar behavior of rubrene‐based single‐crystal OSC with hole (electron) mobility of the order of 1.54 (0.28) cm 2 V −1 s −1 . () In addition, an exhaustive study of charge transport in heterocyclic aromatic compounds were performed by Bredas and coworkers.…”
Section: Introductionmentioning
confidence: 86%
“…For example, the single crystal of pentacene, which is a linearly fused acenes shows field effect mobility of 2.3 cm 2 V −1 s −1 at room temperature on Si/SiO 2 substrate. Similarly, single crystals of tetrabenzotetracene possess highest measured mobility up to 0.81 cm 2 V −1 s −1 . Rubrene, which is an extended tetracene shows ambipolar behavior with single‐crystal hole (electron) mobility of the order of 1.54 (0.28) cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 98%